Towards a multidimensional poverty index for Germany: Parents' employment and children's school success in Germany - Nicolai Suppa (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
This paper compiles a multidimensional poverty index for Germany. Drawing on the capability approach as conceptual framework, I apply the Alkire-Foster method using German panel data. I suggest new operationalizations for two dimensions: social participation and practical reason, the latter drawing on recent findings in experimental economics. The results are consistent with earlier findings, but also reveal several new insights. Specifically, numerous decompositions of the poverty index prove helpful in better tracking and understanding developments. Moreover, I find poor individuals to be adversely affected by general trends in deprivation indicators. Comparing multidimensional and income-based methods, I find only a modest overlap of people considered as poor by both approaches. Moreover, I address the role of income as a dimension in multidimensional poverty indices.
Keywords: I3; I32; D63; H1; 330; multidimensional poverty; Alkire-Foster method; capability approach; SOEP